Bacteriological contamination in soft tissue of the mussel, Perna perna Linnaeus, 1758), on the coastal zone from Bertioga to Peruíbe, São Paulo State (Brazil), - Henriques, Marcelo Barbosa; Zamarioli, Liliana Aparecida; Pereira, Orlando Martins; Faustino, Jussara Silva (Arquivos de Ciências do Mar, 2017)
From September, 1996 to February, 1997 microbiological analyses were performed to identify bacteria of the fecal coliforms group, Vibrio parahaemolyticus, Staphylococcus aureus and Salmonella sp., in the soft tissue of the bivalve Perna perna collected from natural banks in the following cities in the São Paulo State shore: Bertioga, Guarujá, Santos, São Vicente, Praia Grande, Mongaguá, Itanhaém and Peruíbe. Results showed that this bivalve may be considered within the acceptable consumption pattern in only three sites: Guaraú Beach - Peruíbe, Sonho Beach - Itanhaém and Ponta Selada – Bertioga throughout the study period.